The Role of Mentorship in Orthopedic Professional Development: From Training to Mastery - Janki Sharan Bhadani; John Mukhopadhaya (Journal of Orthopaedic Case Reports)
Introduction: Mentorship is essential to the professional and personal development of orthopedic surgeons. It promotes continuous learning, supports career development, and helps develop future leaders in the field. Our study explains key aspects of effective mentorship, differentiates mentorship from coaching, and highlights strategies to enhance mentor–mentee relationships. Materials and Methods: A literature review was conducted to identify best practices in orthopedic mentorship using established models, expert opinions, and real-world training experiences. Results: Strong mentorship positively impacts skill development, career progression, and overall job satisfaction. Key elements include structured guidance, open communication, and mutual commitment. Differences between mentorship and coaching were elucidated, emphasizing their distinct roles in professional development. Discussion: Effective mentorship programs require formal structures, clear expectations, and institutional support. Successful mentor-mentee relationships thrive on trust, regular feedback, and goal alignment. Practical strategies to strengthen mentorship in orthopedic training include mentorship training for faculty, structured pairing programs, and promoting a supportive learning environment. Conclusion: Mentorship is critical in orthopedic education and career development. Establishing strong mentorship programs can enhance learning, improve professional satisfaction, and develop future leaders in the specialty. Institutions should prioritize structured mentorship frameworks to ensure long-term success.